Improving Performance : Foundations of Systemic Performance - Manning, Nick (World Bank, Washington, DC, 2012)
At its heart, a performance orientation in the public sector is a predisposition to make promises and an ability to deliver them. Some of the key ideas behind this are: 1) responsiveness - reducing the time lag between changed political priorities and corresponding public policy actions; 2) measurement - the quantification of outputs (and occasionally outcomes); 3) managerialism - the relaxation of the enforced consistency in procedures to move towards flexibility with accountability in order to improve efficiency. It is often seen purely as an import from the private sector, but in fact there have always been areas of managerialism within the public sector. Using these ideas, this note describes some of the key technical foundations necessary for moving towards a performance orientation and outlines a pragmatic approach for improving performance, highlighting the part played by changing performance arrangements for senior management.